2021
DOI: 10.1089/wound.2020.1206
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Composite Dressings Containing Calcium-Releasing Nanoparticles Accelerate Wound Healing in Diabetic Mice

Abstract: Objective: Wound healing is a complex process that involves the interaction between different cell types and bioactive factors. Impaired wound healing is characterized by a loss in synchronization of these interactions, resulting in nonhealing chronic wounds. Chronic wounds are a socioeconomic burden, one of the most prominent clinical manifestations of diabetes, however, they lack satisfactory treatment options. The objective of this study was to develop polymeric composites that deliver ions having wound hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…A similar strategy in wound treatment has not been addressed before (for a review of current materials, see [ 4 ]). Other strategies, e.g., based on the use calcium-releasing nanoparticles such as CaP ormoglass (organic modified calcium phosphate glass; [ 37 ]) also showed an accelerating effect on chronic wound healing [ 40 ], but these strategies lack the energy-providing effect of polyP. In principle, polyP alone in the form of Ca-polyP nanoparticles has also a stimulatory effect on wound healing, as shown previously [ 22 ]; however, in this case, after the ALP-mediated degradation of this molecule, no calcium-releasing store remains that can maintain the wound-healing effect of calcium ions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar strategy in wound treatment has not been addressed before (for a review of current materials, see [ 4 ]). Other strategies, e.g., based on the use calcium-releasing nanoparticles such as CaP ormoglass (organic modified calcium phosphate glass; [ 37 ]) also showed an accelerating effect on chronic wound healing [ 40 ], but these strategies lack the energy-providing effect of polyP. In principle, polyP alone in the form of Ca-polyP nanoparticles has also a stimulatory effect on wound healing, as shown previously [ 22 ]; however, in this case, after the ALP-mediated degradation of this molecule, no calcium-releasing store remains that can maintain the wound-healing effect of calcium ions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, calcium is a stimulator of angiogenesis both in vitro and in vivo [ 35 , 36 , 37 ]. The acceleration of wound healing, especially in chronic wounds, has been demonstrated by the use of calcium alginate dressings [ 38 , 39 ] or dressings containing calcium-releasing nanoparticles [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DFO and copper synergistically upregulated the expression of HIF-1α and VEGF, thereby regulating angiogenesis [ 167 ]. Soledad Perez-Amodio et al prepared poly(lactic acid) (PLA) fiber matrices loaded with calcium-releasing nanoparticles (SG5) (PLA-SG5) and experimentally demonstrated that this compound material stimulates angiogenesis, collagen synthesis, and granulation tissue formation and accelerates wound closure in the ischemic wounds of diabetic mice [ 264 ]. Of note, the metals mentioned above can avoid drug resistance and promote wound healing through different mechanisms.…”
Section: Bioactivators For Dusmentioning
confidence: 99%
“…• Timing 26 hours, 1.5-hours hands-on time 24. Collect mice wound healing assay tissue samples by tissue excision 14 days after generation of pressure ulcers (6 days) and wound treatment (8 days) with poly-lactic acid (PLA) or Mepilex® (Control) wound dressings, following the protocol described by Pérez-Amodio et al 46 . 25.…”
Section: Sample Preparationmentioning
confidence: 99%